2010
DOI: 10.2478/v10042-009-0077-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum sICAM, sVCAM and sE-selectin levels in colorectal cancer patients.

Abstract: Abstract:Colorectal cancer (CRC) is one of the most common cancers of the gastrointestinal tract and the fourth cause of cancers death in the world. Soluble adhesion molecules (CAMs) are thought to have an important role in host defense against carcinogenesis. They are biomarkers of inflammation and indicators of the immune response to tumors. The study included 40 CRC patients without remote metastases and 24 control subjects. Serum concentrations of sE-selectin, sICAM and sVCAM in patients with CRC were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…These findings suggested that the levels of sE-selectin can predict tumor invasion and progression. No association was found between sE-selectin and metastasis and certain studies also failed to demonstrate an association between sE-selectin and lymph node metastasis (33). Other studies indicated that sE-selectin is not able to predict the metastasis of colorectal cancer (34).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…These findings suggested that the levels of sE-selectin can predict tumor invasion and progression. No association was found between sE-selectin and metastasis and certain studies also failed to demonstrate an association between sE-selectin and lymph node metastasis (33). Other studies indicated that sE-selectin is not able to predict the metastasis of colorectal cancer (34).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Cellular adhesion molecules manage the interactions between cells and are therefore essential during the development and maintenance of the tissue architecture (15). ICAM-1 has received increased attention in cancer biology.…”
Section: Discussionmentioning
confidence: 99%
“…Higher amounts of ICAM-1 were found in well-differentiated compared to lower levels in poorly differentiated tumors (16). In contrast, the soluble form of ICAM-1 (sICAM-1) is significantly correlated with tumor stage and the development of metastasis, not only in CRC (13,15,(18)(19)(20) but also in other cancers such as gastric cancer (21,22), breast cancer (23)(24)(25), urological malignancies (26), malignant melanoma (27), lung cancer (28), hepatocellular cancer (29) and chronic B-lymphocytic leukemia (30). At present, the source of sICAM-1 is unclear (13,22) but it may be produced by proteolytic cleavage of membrane-bound ICAM-1 (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations